2019
DOI: 10.1007/s10955-019-02295-3
|View full text |Cite
|
Sign up to set email alerts
|

Translationally Invariant Universal Classical Hamiltonians

Abstract: Recent work has characterised rigorously what it means for one quantum system to simulate another, and demonstrated the existence of universal Hamiltonians-simple spin lattice Hamiltonians that can replicate the entire physics of any other quantum many body system. Previous universality results have required proofs involving complicated 'chains' of perturbative 'gadgets'. In this paper, we derive a significantly simpler and more powerful method of proving universality of Hamiltonians, directly leveraging the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(155 reference statements)
0
9
0
Order By: Relevance
“…The original proof actually demonstrates that AME(2m, q) states are the purification of a threshold quantum secret sharing (QSS) scheme, however every pure QSS scheme is equivalent to a quantum MDS code [7] so the result follows immediately. 27 The proof of this theorem is a straightforward generalisation of [25,Theorem 2] which will give:…”
Section: B (Pseudo-)perfect Tensors and Quantum Error Correcting Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…The original proof actually demonstrates that AME(2m, q) states are the purification of a threshold quantum secret sharing (QSS) scheme, however every pure QSS scheme is equivalent to a quantum MDS code [7] so the result follows immediately. 27 The proof of this theorem is a straightforward generalisation of [25,Theorem 2] which will give:…”
Section: B (Pseudo-)perfect Tensors and Quantum Error Correcting Codesmentioning
confidence: 99%
“…The existence of translationally invariant universal quantum Hamiltonians is an open question (in the classical case it has been shown that translationally invariant universal Hamiltonians do exist [27]). If translationally invariant universal quantum models were found it may be possible to construct a HQECC where the boundary Hamiltonian exhibits full translational invariance.…”
Section: G Translational Invariance In the Boundary Modelmentioning
confidence: 99%
“…This fact reflects the intrinsic computational power of near-neighbor interactions. In fact, Ising models have been shown to be universally complete [13,14], with a map between any given logic circuit to the ground states of some 2D Ising model Hamiltonian.…”
Section: Critical Phenomena and The 2d Ising Modelmentioning
confidence: 99%
“…But this has sown the ground for many other results: An important one would be a rigorous comparison between universal spin models [16] and universal Turing machines. (Note that translationally invariant universal classical spin Hamiltonians have also been shown to exist [17]). For example, universal spin models allow for a full characterisation [16,Theorem 15], but universal Turing machines do not, due to Rice's Theoremthus, the two notions of universality do not seem to be equivalent.…”
Section: Discussionmentioning
confidence: 99%